The effect of theobromine and NaF 2% exposure to enamel surface hardness after immersing in orange juice beverage - Tamara Yuanita; Setyabudi Setyabudi; Qintan Sekar Adjani (Conservative Dentistry Journal, 2019)
Background: Consumption of orange juice which had acidic quality will cause a demineralization on enamel. The most effective way to prevent the demineralization process was by involving remineralization agents. Fluoride was effective to improve remineralization but has toxicity effect and caused fluorosis at certain dose. Another alternative for remineralization agent without providing side effects is theobromine contained in cocoa peel extract (Theobroma cacao). Objective: To explain the effect of theobromine and NaF 2% exposure on enamel surface hardness after immersion in commercial orange juice. Method: Twenty-seven cattle incisors were cut into a square shape 1x1 cm and then planted in a round resin mold then divided into three groups. All three groups were immersed in orange juice beverage for 60 minutes. The control group was immersed in distilled water, group I was given theobromine 200 mg / L, and group II was given 2% NaF after exposure for 96 minutes. Surface hardness measurements were carried out using the Wolpert Micro Vickers Testers tool. Results: There was a significant difference (p <0.05) between surface hardness of tooth enamel from the control group and theobromine group and there was also a significant difference between the control group and the NaF group. However, there was no significant difference (p> 0.05) in the NaF group with theobromine group. Conclusion: The effect of exposure to theobromine and NaF 2% on surface enamel hardness after immersion in orange juice beverage has the same result.